Management of Combat Vascular Injuries Using Modern Imaging: Are We Getting Better?. (10th January 2013) - Nitecki, Samy S.; Karram, Tony; Ofer, Amos; Engel, Ahuva; Hoffman, Aaron
Abstract : Background . Vascular injuries often result in life threatening hemorrhage or limb loss. When they present with a single entry or exit wound, surgery is immediately indicated. With multiple injuries, however, imaging such as CTA is necessary for diagnosis and choice of treatment. Methods . For all combat-related vascular cases admitted to our medical center during the Lebanon wars in 1982 and 2006, we compiled and compared presenting signs and symptoms, means of diagnosis, treatments, and results. Results . 126 patients with vascular injuries were admitted (87 in 1982, 39 in 2006). 90% were male; mean age of 29 years (range 20–53). All injuries were accompanied by insult to soft tissue, bones, and viscera. 75% presented with injury to arteries in the extremities. 75% of these patients presented with limb ischemia, and 25% sustained massive blood loss. Treatments included venous interposition graft, end-to-end anastomosis, venous patch, endovascular technique (only in 2006), and ligation/observation. Complications included thrombosis and wound infections. Mortality and amputations occurred only in 1982, and this may be attributed to the use of imaging, advanced technique, and shorter average time from injury to hospital (7 hours). Conclusions . We recommend CTA as the first line modality for diagnosis of vascular injuries, as its liberal use allowed for early and appropriate treatment. Treatment outcomes improved with fast and effective resuscitation, liberal use of tourniquets and fasciotomies, and meticulous treatment by a multidisciplinary team.